2018
DOI: 10.3389/fmicb.2018.00807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Functionally Unknown Arginine–Aspartate–Aspartate Family Protein From Halobacillus andaensis and Functional Analysis of Its Conserved Arginine/Aspartate Residues

Abstract: Arginine–aspartate–aspartate (RDD) family, representing a category of transmembrane proteins containing one highly conserved arginine and two highly conserved aspartates, has been functionally uncharacterized as yet. Here we present the characterization of a member of this family designated RDD from the moderate halophile Halobacillus andaensis NEAU-ST10-40T and report for the first time that RDD should function as a novel Na+(Li+, K+)/H+ antiporter. It’s more interesting whether the highly conserved arginine/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 66 publications
(152 reference statements)
3
19
0
Order By: Relevance
“…Most bacteria were predicted to contain 5–9 distinct single-gene or multiple-gene Na + /H + antiporters ( Krulwich et al, 2009 ; Mesbah et al, 2009 ). However, we speculate that halophiles may have evolved significantly more Na + /H + antiporters including even unreported ones to exhibit high capability of halo-alkaline tolerance, which has been demonstrated by our recent reports on several novel Na + /H + antiporters from the different moderate halophiles ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ). In these studies, we found that the members of three functionally uncharacterized families such as UPF0118, DUF1538 and RDD display Na + (Li + )/H + or Na + (Li + , K + )/H + antiport activity ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Most bacteria were predicted to contain 5–9 distinct single-gene or multiple-gene Na + /H + antiporters ( Krulwich et al, 2009 ; Mesbah et al, 2009 ). However, we speculate that halophiles may have evolved significantly more Na + /H + antiporters including even unreported ones to exhibit high capability of halo-alkaline tolerance, which has been demonstrated by our recent reports on several novel Na + /H + antiporters from the different moderate halophiles ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ). In these studies, we found that the members of three functionally uncharacterized families such as UPF0118, DUF1538 and RDD display Na + (Li + )/H + or Na + (Li + , K + )/H + antiport activity ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 52%
“…However, we speculate that halophiles may have evolved significantly more Na + /H + antiporters including even unreported ones to exhibit high capability of halo-alkaline tolerance, which has been demonstrated by our recent reports on several novel Na + /H + antiporters from the different moderate halophiles ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ). In these studies, we found that the members of three functionally uncharacterized families such as UPF0118, DUF1538 and RDD display Na + (Li + )/H + or Na + (Li + , K + )/H + antiport activity ( Dong et al, 2017 ; Meng et al, 2017 ; Shao et al, 2018 ). Although a random screening method by functional complementation with E. coli KNabc helped us find out their functions as Na + /H + antiporters, we suspect that these ever uncharacterized proteins may possess the additional functions, whose function predictions are, to great extent, restricted by limited bioinformatic knowledge about these uncharacterized proteins with no or significantly low sequence identity with their homologs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Himar1 intragenic insertion mutants were also identified in genes for vitamin synthesis [thiamine biosynthesis protein ThiC (Lawhorn et al, 2004) and dethiobiotin synthase (Otsuka et al, 1988)], mutation repair [RmuC (Slupska et al, 2000), DNA mismatch repair proteins MutS and MutL (Mansour et al, 2001)], transcriptional regulation [DNA-3-methyladenine glycosylase (Wyatt et al, 1999), transcriptional regulator NrdR (Torrents et al, 2007)], nutrient transport [sodium:alanine symporter family protein (Khani et al, 2018), and two MFS transporters (Quistgaard et al, 2016)], bacterial division and chromosomal segregation [chromosome partitioning ATPase ParA (Lutkenhaus, 2012), cell division ZapA family protein (Small et al, 2007)], and others [amidophosphoribosyltransferase ComF (Bhagavan and Ha, 2015), tellurium resistance protein TerC (Turkovicova et al, 2016), RDD family protein (Shao et al, 2018), glutathione S-transferase (Nebert and Vasiliou, 2004), aspartate kinase (Min et al, 2015), gamma carbonic anhydrase family protein (Hewett-Emmett and Tashian, 1996), octaprenyldiphosphate synthase (Ashby and Edwards, 1990)] ( Table 1). These genes are apparently not required for HF strain infection of macrophages.…”
Section: Ehrlichia Sp Hf Strain Himar1 Insertional Mutant Librarymentioning
confidence: 99%
“…E. coli CM2 or KNabc transformants were used to prepare the everted membrane vesicles by the French press method as described in our recent studies (Dong et al, 2017;Meng et al, 2017;Shao et al, 2018;Xu et al, 2019). Briefly, cultures were harvested and crushed by one passage under high pressure.…”
Section: Preparation Of Everted Membrane Vesiclesmentioning
confidence: 99%